Penentuan Parameter Setting Mesin Pada Proses Corrugating - Sylvia Ongkowijoyo; Ig. Jaka Mulyana; Julius Mulyono (Media Teknika, 2016)
Corrugating process is the process in making carton box which is merging the top sheet of kraft paper (top liner), wave paper (paper medium) and kraft paper bottom (bottom liner) using glue. Output of corrugating process is corrugated sheet. The parameter of quality corrugated sheet is bursting strength. In the corrugating process, the value of bursting strength is influenced two factors: the speed and temperature of corrugator. In this study, we discuss the experiment to determine level of corrugator speed and temperature that can produce the maximum bursting strength. Response Surface Methodology (RSM) is used to design of experiment and analysis. RSM able to identify points outside the experimental area (order model I) and determine the point of maximum response with the method of steepest ascent, and may explain the relationship of quantitative independent variable responses (order model II). The result of this study is that optimum levels engine speed is 178 m / min and level temperature of 174.9 C. The optimum level of value response bursting strength of 13.8 kgf /mm2.